Konsep Pendidikan Nilai (Akhlak) Berdasarkan Perspektif Sa’id Hawwa Dan Imam Al Ghazali - Muhammad Rofiq; Isnaeni Nur Khasanah; Sani Fitri Nur Laela; Mukh Nursikin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This study aims to combine teh thoughts of Sa’id Hawwa and Imam Al-Ghazali about the concept of value education (morals). This research is considered important considering the serious ethical problems faced by modern society. By using the content analysis method, this study produced a number of findings, namely the concept of value education (morals) according to the two figures above. According to Sa’id Hawwa, that is to shape the child’s personality in an islamic way so that he has a solid moral base and islmic khowledge. In addition, the basics of moral according to Sa’id Hawwa are loyalty only to Allah, the messenger of Allah and the believers; and strive in the way of Allah. As for the concept of Imam Al-Ghazali’s thoughts on value education (morals) in children, including morals to god, morals to parents, morals to oneself and morals to others. As for morals, the highest goal of religion and morals is to achieve happiness in the world and hereafter, perfection of the soul for individuals and to create happiness, prgress, strength and steadfastness for society.